A net-zero future needs hydrogen not less than batteries, especially for urban air mobility. (12th August 2022) - Boretti, Alberto
Highlights: Progress towards net zero faster considering more synergetic approaches than just one solution. Hydrogen and battery energy storage are synergetic ingredients of future electric UAM. Hydrgen fuel cell-battery integration is key to development of better electric UAM.